Analisis Perbandingan Tarif Jasa Rawat Inap dengan Menggunakan Traditional Costing System dan Activity Based Costing System (Studi Kasus Pada RSU Mitra Medika Amplas Medan) - Nurhidayah Nurhidayah; Saparuddin Siregar; Wahyu Syarvina (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2026)
This study aims to find out how to determine inpatient service rates using traditional costing systems and activity-based costing at Mitra MedikaAmplas Public Hospital, how to compare the results of calculating inpatient service rates using traditional costing systems and activity-based costing. The object of this research is RSU Mitra Medika Amplas. This study uses qualitative methods with comparative studies, data collection techniques by means of observation and interviews. The types of data used are primary data and secondary data which are cost data for 2020. The results of this study indicate that the application of the traditional costing system in determining inpatient service rates produces distorted cost information. Calculation errors can be minimized by implementing an activity-based costing system. There are differences in the results of calculations using the traditional costing system and the activity-based costing method, where the results of calculations using activity-based costing are cheaper than the results of calculations using the traditional costing system.